Pengaruh Pelatihan, Kepuasan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan pada DPTR Kabupaten Sleman - Hanifah Hidayatul M; Jumadi Jumadi (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this research is to determine the simultaneous and partial effects of training, job satisfaction, and work motivation on employee performance at the Land and Spatial Planning Office of Sleman Regency. The research method used is the quantitative method. The population in this study consists of 71 employees, with a sample size of 60 respondents determined using the Slovin formula. The sampling technique used is non-probability sampling with an accidental sampling approach. Data were collected using a questionnaire and analyzed using SPSS version 23. The research results show that training affects employee performance because the t-value obtained is 3.252 > t-table 2.003 with a significance value of 0.002 < 0.05, job satisfaction affects employee performance because the t-value obtained is 4.282 > t-table 2.003 with a significance value of 0.000 < 0.05, and work motivation affects employee performance because the t-value obtained is 2.930 > t-table 2.003 with a significance value of 0.005 < 0.05. Meanwhile, training, job satisfaction, and work motivation together affect employee performance because the f-value obtained is 28.785 > f-table 2.766 with a significance value of 0.000 < 0.05.